EFFECT OF SILICA COATING IN ACRYLIC ARTIFICIAL TEETH ON SURFACE ROUGHNESS, CONTACT ANGLE, AND GROWTH OF STREPTOCOCCUS MUTANS - Maharani, Adella Syvia; Aditama, Pramudya; Indrastuti, Murti; Saleh, Suparyono (Faculty of Dentistry, Universitas Islam Sultan Agung, 2021)
ABSTRACTBackground: Acrylic resin artificial teeth is easily to have bacterial adhesion. It is necessary to perform a treatment on that surface, in order to reduce bacterial adhesion. This study aimed to reveal the effect of silica coating in acrylic resin artificial teeth on surface roughness, contact angle measurement, and the growth of Streptococcus mutans.Method: The study was conducted on two groups (n=16) of disk-shaped acrylic resin artificial teeth with a diameter of 10 mm and thickness of 2 mm. A 2% silica coating material was obtained by diluting 2 g silica nanoparticles on 100 ml of ethanol. Surface roughness, contact angle measurement, and the growth of Streptococcus mutans was measured using surface roughness measuring instrument, camera digital, and colony counter. The data obtained were then analyzed using T-test (p<0.05).Result: The results showed that the surface roughness and contact angle measurement in group I (0.29±0.08 μm); (79,49º ± 10,88º) was higher than group II (0.17±0.05 μm); (34,77º±0,05º). The growth of Streptococcus mutans in group I was also higher (32.28±3.75 CFU/ml) than group II (24.83±3.47 CFU/ml). Conclusion: The study concluded that there is an effect of silica coating on surface roughness, contact angle measurement, and the growth of Streptococcus mutans in acrylic resin artificial teeth.